2006
DOI: 10.1590/s1519-38292006000200002
|View full text |Cite
|
Sign up to set email alerts
|

Sistemas de informação em saúde e monitoramento de morbidade materna grave e mortalidade materna

Abstract: During the last decades there was a huge decrease of maternal mortality in developed countries, while in developing countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0
18

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
2
2
0
18
Order By: Relevance
“…Also, two thirds of the SIM records that were found in SIH had diagnoses and procedures relating to at least one severe maternal morbid condition, which perhaps could be explored as a predictor for maternal death. In reviews on maternal mortality and severe maternal morbidity, 13,14 it has been suggested that women who died or who suffered severe worsening of health associated with pregnancy might have similar characteristics, in accordance with some published studies. 11,16 Future studies based on hospital records may be able to better explore the situations of maternal mortality and severe maternal morbidity.…”
Section: Discussionsupporting
confidence: 60%
“…Also, two thirds of the SIM records that were found in SIH had diagnoses and procedures relating to at least one severe maternal morbid condition, which perhaps could be explored as a predictor for maternal death. In reviews on maternal mortality and severe maternal morbidity, 13,14 it has been suggested that women who died or who suffered severe worsening of health associated with pregnancy might have similar characteristics, in accordance with some published studies. 11,16 Future studies based on hospital records may be able to better explore the situations of maternal mortality and severe maternal morbidity.…”
Section: Discussionsupporting
confidence: 60%
“…Uma das razões para a precária sensibilidade do SIH-SUS como estratégia alternativa para o monitoramento do near miss materno parece ser o limite percentual de cesarianas estipulado para o reembolso pelo SUS 14,15,16,17,18 , que no Estado do Rio de Janeiro é de 27% de partos cesáreos por unidade de saúde 28 . Segundo os achados do presente estudo, a não consolidação no SIH-SUS das AIH referentes a pelo menos quatro (14,8%) dos 27 eventos de near miss ocorreu em virtude desse limite.…”
Section: Discussionunclassified
“…Frente ao elevado custo operacional para a identificação dos casos de near miss a partir do seguimento prospectivo ou revisão dos prontuários médicos, diversos autores têm proposto a utilização das informações obtidas nas bases de dados administrativas como alternativa para a vigilância dos casos de morbidade materna e near miss 15,16,17,18 . Entretanto, a maior parte dessas publicações têm se valido de reflexões teóricas sobre essa estratégia 15,18 , ou projetado incidên-cias de morbidade materna e near miss sem uma avaliação preliminar de sua validade 17 .…”
unclassified
See 2 more Smart Citations